Identification and quantitation of phenolic compounds in faecal matrix by capillary gas chromatography and nano‐electrospray mass spectrometry - Knust, Ulrike; Erben, Gerhard; Spiegelhalder, Bertold; Bartsch, Helmut; Owen, Robert (Rapid communications in mass spectrometry, 2006)
Very few relevant methods have been described for the detection and quantitation of phenolic compounds in faecal matrix. Extraction with conventional organic solvents such as chloroform/methanol (2:1, Folch reagent), methanol and ethanol (72%) showed high extraction efficiency for lipids and also gave good recovery of the major phenolic compounds present in the matrix.